2013 European guideline on the management of lymphogranuloma venereum. (24th March 2014) - de Vries, H.J.C.; Zingoni, A.; Kreuter, A.; Moi, H.; White, J.A.
Abstract What is new in this updated guideline? This is the update version of the 2010 European guideline on the management of lymphogranuloma venereum (LGV). New issues are: Epidemiology Based on clonal relatedness of prevalent LGV strains there is evidence that the LGV epidemic among men who have sex with men (MSM) in the Western world prevailed already in the United States in the 1980s and was introduced into Europe by the end of the last century. Aetiology and transmission A new LGV variant causing severe proctitis was unveiled and designated L2c. The L2b LGV variant causing the vast majority of infections among MSM is now also found among a few heterosexual women. Management Apart from HIV and STI screening, Hepatitis C Virus (HCV) testing should be offered to all LGV patients. To exclude reinfections, STI screening during a follow‐up visit 3 months after an LGV diagnosis should be offered.